KONSEP PENDIDIKAN ISLAM MENGENAI AKHLAK PERSPEKTIF AL GHAZALI (KAJIAN KITAB IHYA’ ULUMUDDIN) - Ahmad Budiyono (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2019)
Behavior education is important to learn not only in formal but also in non formal education, such as in family. The behavior concept has been formulated by many schoolars. One of them was Imam al Ghazali. The researcher raises the the al Ghazali thought who is classic figure known as theologist, philoshopher and sufi from sunni. Behavior education as explained in Ihya’ Ulumuddin book is prioritized to formulate students’ moral. He discussed some such behavior education, as moral to them selves that is eating and drinking, moral respect to visitors, in trading, in socialization. The morals as if refer to material, but it refers to the future. To implement those moral correctly, it needs some methods for example habitual, modelling, and story telling.